PAK5 is a potential target in myelodysplastic syndrome through interacting with LMO2 and GATA1: PAK5 interacts with LMO2 and GATA1 in MDS - Pan, Xiaoyan; Liu, Dawei; Ying, Minchao; Zheng, Gaoming; Fan, Chaoming; Pan, Feng; Ke, Qiang (Cellular and Molecular Biology, 2022)
Myelodysplastic syndrome (MDS) is a neoplastic heterogeneous and pre-leukemic disease with poor clinical outcome due to the failure of current chemotherapeutic strategies to target leukemic stem cells. Recently, we find that p21-activated kinase 5 (PAK5) overexpresses in MDS patients and leukemia cell lines. The clinical and prognostic value of PAK5 in MDS is unclear although it has anti-apoptosis ability and can promote cell survival and mobility in solid tumors. In this study, we find that LMO2 is co-expressed with PAK5 in the aberrant cells from MDS, and mitochondria-localized PAK5 can translocate into cell nucleus upon fetal bovine serum stimulation to interact with LMO2 and GATA1, which are important transcription regulators in hematological malignancies. Interestingly, without LMO2, PAK5 fails to bind GATA1 and facilitate GATA1 Ser161 site phosphorylation, indicating that PAK5 may be a key kinase in LMO2-associated hematopoietic diseases. Moreover, we find that PAK5 protein level in MDS is significantly higher than leukemia, and the data of 2095 leukemia samples from ‘BloodSpot’ database shows that PAK5 mRNA level in MDS is also increased obviously. Taken together, our findings suggest that PAK5-targeted strategies in clinical therapy have a potential value on MDS intervention.